Management of endocrine conditions at the end of life. (2nd May 2020) - de Bray, Anne; Tomas, Jon; Gittoes, Neil; Hassan-Smith, Zaki
Abstract: An important facet to end-of-life care is deprescribing. This can be challenging when reviewing life-sustaining endocrine medications but, unlike for diabetes, there is no national guidance to support patients and clinicians faced with care planning. This article reviews the limited current evidence to highlight areas for further discussion and research with the aim of moving towards consensus opinion. Discontinuation of certain endocrine medications, including corticosteroids, desmopressin and levothyroxine, is likely to precipitate an 'endocrine-driven mechanism of death', while it may be reasonable to discontinue other endocrine medications without the risk of hastening death or causing unnecessary symptoms. However, the over-arching theme should be that early discussion with patients regarding conversion or discontinuation of endocrine medications or monitoring is central to care planning.